Risk of muscle damage with blood flow-restricted exercise should not be overlooked - Wernbom, M.; Paulsen, G.; Bjørnsen, T.; Cumming, K; Raastad, T. (Clinical Journal of Sport Medicine, 2021)
Resistance exercise with low loads combined with blood flow restriction (BFR) has been shown to induce increases in muscle size comparable with those seen with conventional heavy resistance exercise in untrained individuals. The low loads used, typically between 20% and 50% of 1 repetition maximum (1RM), make blood flow-restricted resistance exercise (BFRRE) an attractive training modality for individuals who may not tolerate high musculoskeletal forces (eg, clinical patient groups and frail older adults). We conclude that there is sufficient evidence from case studies and controlled experiments to state that very strenuous BFRRE, much like eccentric exercise, can induce several signs and symptoms of muscle damage and in some cases rhabdomyolysis in healthy but unaccustomed subjects. We maintain that BFRRE should be introduced carefully and gradually to allow for the repeated-bout effect to take place and avoid risking unnecessary muscle damage and stress.